2021
DOI: 10.1002/mabi.202100162
|View full text |Cite
|
Sign up to set email alerts
|

Natural Glycan Derived Biomaterials for Inflammation Targeted Drug Delivery

Abstract: Inflammation is closely related to a variety of fatal or chronic diseases. Hence, targeting inflammation provides an alternative approach to improve the therapeutic outcome of diseases such as solid tumors, neurological diseases, and metabolic diseases. Polysaccharides are natural components with immune regulation, anti‐virus, anti‐cancer, anti‐inflammation, and anti‐oxidation activities. Herein, this review highlights recent progress in the polysaccharide‐based drug delivery systems for achieving inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 119 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Relevant animal experiments have shown that ephedra polysaccharides can improve lung disease injury and inhibit inflammation, apoptosis, and oxidative stress by regulating the level of immune cells such as T helper cells. Codium fragile polysaccharide can induce the activation of mouse dendritic cells in vivo and directly induce natural killer cells to produce IFN-γ in vitro, thereby promoting the apoptosis of target cells and contributing to immune anti-cancer[ 23 - 25 ].…”
Section: Mechanism Of Action and Intervention Strategies Of Common Im...mentioning
confidence: 99%
“…Relevant animal experiments have shown that ephedra polysaccharides can improve lung disease injury and inhibit inflammation, apoptosis, and oxidative stress by regulating the level of immune cells such as T helper cells. Codium fragile polysaccharide can induce the activation of mouse dendritic cells in vivo and directly induce natural killer cells to produce IFN-γ in vitro, thereby promoting the apoptosis of target cells and contributing to immune anti-cancer[ 23 - 25 ].…”
Section: Mechanism Of Action and Intervention Strategies Of Common Im...mentioning
confidence: 99%
“…Natural and synthetic polymers, each with distinct advantages and limitations, are integral to the development of biomedical materials for bone tissue engineering. Natural polymers, including chitosan, alginate, gelatin, glycosaminoglycan, collagen, fibrin and hyaluronic acid, possess structural and biochemical properties similar to those of the natural bone organic matrix [ 36 , 37 ]. Some are extensively employed in creating bio-dental materials for oral drug delivery, periodontitis treatment via bone tissue engineering and dentin-pulp regeneration [ 38 ].…”
Section: Classification Of Current Bone Repair Materialsmentioning
confidence: 99%
“…These innovations leverage the epithelial enhanced permeability and retention (eEPR) effect to precisely target inflammatory tissues. [25,26] Micro-/nanoparticles can passively accumulate within inflamed colonic tissues, exploiting increased vascular network permeability, disruptions in intercellular connections, and mucous layer damage. [27] Furthermore, the UC microenvironment, characterized by reduced pH levels, heightened levels of reactive oxygen species, and overexpressed enzymes (𝛼-amylase, neutrophil elastase, myeloperoxidase, etc.…”
Section: Introductionmentioning
confidence: 99%